A Planned Multidisciplinary Surgical Approach to Treat Primary Pelvic Malignancies - Andrea Sambri; Michele Fiore; Matteo Rottoli; Giuseppe Bianchi; Marco Pignatti; Marta Bortoli; Amelio Ercolino; Stefano Ancetti; Anna Myriam Perrone; Pierandrea De Iaco; Riccardo Cipriani; Eugenio Brunocilla; et al. (Current Oncology, 2023)
The pelvic anatomy poses great challenges to orthopedic surgeons. Sarcomas are often large in size and typically enclosed in the narrow confines of the pelvis with the close proximity of vital structures. The aim of this study is to report a systematic planned multidisciplinary surgical approach to treat pelvic sarcomas. Seventeen patients affected by bone and soft tissue sarcomas of the pelvis, treated using a planned multidisciplinary surgical approach, combining the expertise of orthopedic oncology and other surgeons (colleagues from urology, vascular surgery, abdominal surgery, gynecology and plastic surgery), were included. Seven patients were treated with hindquarter amputation; 10 patients underwent excision of the tumor. Reconstruction of bone defects was conducted in six patients with a custom-made 3D-printed pelvic prosthesis. Thirteen patients experienced at least one complication. Well-organized multidisciplinary collaborations between each subspecialty are the cornerstone for the management of patients affected by pelvic sarcomas, which should be conducted in specialized centers. A multidisciplinary surgical approach is of paramount importance in order to obtain the best successful surgical results and adequate margins for achieving acceptable outcomes.